Sustainable Tourism Marketing in the Digital Age - Imelda Regina Pellokila; Damianus Sonny Lamoren; Padre Pio C. I. Fallo (Univiversitas Dr. Djar Wattiheluw, 2024)
This study examines a sustainable tourism marketing strategy for Kupang City, NTT, which faces low tourist arrivals despite its significant potential. Using a qualitative approach, including in-depth interviews with 10 key informants and field observations, three main challenges were identified: suboptimal use of digital technology, limited local community involvement, and insufficient competence among tourism marketing human resources. The study proposes several recommendations, including an integrated digital marketing strategy, community empowerment programs, improved HR competencies, the development of a monitoring and evaluation system, and enhanced stakeholder collaboration. This research offers both theoretical and practical insights into sustainable tourism marketing strategies for small towns in developing countries, with important implications for policymakers and tourism industry stakeholders in Kupang City.